Estudo do desgaste de ferramentas de metal duro e cerâmicas no torneamento do Inconel® 751 e Inconel® 718 - Lima, Fábio de Freitas (2012)
Nickel alloys present high mechanical resistance at elevated temperatures, high creep and fatigue resistances besides of excellent corrosion resistance that makes them interesting for applications in the aerospace industry. The present work investigates the wear types and their evolution during machining of Inconel® 751 and Inconel® 718 alloys. The related wear mechanisms were also studied, as well as the tool damages generated during the cutting process. Matrixes were built with three types of ceramic tools: SiAlON, Mixed and Whisker and three types of cemented carbide tools: WC/Co, WC/Co 6% coated with TiAlN and WC/Co 10% coated with TiAlN using Design of Experiments Techniques DOE considering the following input variables: cutting speed, tool geometry and the lubri-cooling atmosphere. During these tests the workpiece surface roughness and the cutting force components were measured. The analysis of the results showed that all the studied variables have influenced the wear types. Notch wear was observed mainly at low cutting speeds for the Inconel® 751, followed by the average flank wear and nose wear which were not influenced by the lubri-cooling atmosphere as weren t the tool lives. The wear mechanisms involved were attrition (adhesion), abrasion and diffusion. The surface roughness and the cutting force components showed direct relationship with the tool wear.